Complications and Influential Perioperative Factors Associated with SpaceOAR Hydrogel Placement - Kerith R. Wang; Rishabh K. Simhal; Cassra B. Clark; Mark J. Mann; James R. Mark; Costas D. Lallas; Robert Den; Edouard J. Trabulsi (Advances in Urology)
Objective. To examine one academic institution’s experiences with SpaceOAR placement, its associated complications, and periprocedural characteristics that affect outcomes for the purpose of quality improvement. Materials and Methods. We conducted a retrospective review of 233 patients who received SpaceOAR from four surgeons and one radiation oncologist between 2018 and 2021. Variables such as demographics, oncologic parameters, radiation plan, and radiographic assessment of hydrogel placement were recorded. The Charlson Comorbidity Index (CCI) was used to assess comorbidity risk. Mann–Whitney and Fisher’s exact tests were performed to compare patients with and without complications. Results. Of the 233 patients who received SpaceOAR, 24 (10.3%) experienced toxicity. All complications were Clavien I or II, such as pelvic pain postplacement, pelvic fullness, bleeding, and lower urinary tract symptoms. 16 patients (6.9%) had some portion of the hydrogel injected into the rectal wall, but it was never clinically significant. The average CCI was 3.2 ± 0.95 for patients who experienced complications; the average CCI was 3.6 ± 1.6 (p=0.48) in the group without complications. Of the physicians with higher procedure volumes, Physician #1 had the highest rate of patient-reported complications at 11 out of 68 (16.2%) and Physician #2 had the lowest rate of complications at 4 out of 96 placements (4.2%). Multivariate analysis found that patients who had received hormone therapy previously had less odds of reporting complications after SpaceOAR placement. Conclusions. The listed attending on the procedure had a significant correlation to complications with SpaceOAR placement on univariate analysis, and hormone therapy had some benefits to the tolerance for the procedure on multivariate analysis. Overall, the hydrogel placement was well tolerated with low incidence of mild and transient procedure-related toxicity.